2010
DOI: 10.1159/000316321
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lupus Nephritis by Mycophenolate Mofetil

Abstract: Background/Aims: Mycophenolate mofetil (MMF) has been increasingly used for the treatment of lupus nephritis (LN). The aim of this study was to examine the efficacy and safety of MMF used with low doses of corticosteroids as maintenance therapy in patients with LN. Methods: The study covered 35 patients, most of them with proliferative types of LN (5 WHO class III, 26 class IV), while 1 had class V and 3 class VI nephritis. MMF was administered in the dose of 1.5–2 g/24 h and prednisone at 10–20 mg/day. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…During the last decade, the results of at least 9 trials have been reported [8,9,11,12,13,14,15,16,17], and several retrospective studies [18,19,20] have focused on the best drug schedule in the maintenance phase of treatment of LN. The results allow us to conclude that short-term induction with intravenous CYC followed by maintenance therapy with MF or AZA was more efficacious than other treatment schedules [11,12,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, the results of at least 9 trials have been reported [8,9,11,12,13,14,15,16,17], and several retrospective studies [18,19,20] have focused on the best drug schedule in the maintenance phase of treatment of LN. The results allow us to conclude that short-term induction with intravenous CYC followed by maintenance therapy with MF or AZA was more efficacious than other treatment schedules [11,12,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies analyze patients with normal renal function [8,13,18,19,20], and only two included cases with elevated serum creatinine and/or decreased eGFR at the initiation of maintenance therapy with MF [9,11]. However, no studies include subanalyses of the effect of baseline renal function on renal relapse and response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with previous studies. 24,26,27 This can be explained by the fact that lupus nephritis is more common in young females.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular nephritis is a type of diffuse or focal autoimmune disease characterized by glomerular damage (1). Clinical manifestations include edema, abnormal urine (proteinuria, hematuria), anemia, renal dysfunction and difficult treatment; with disease migration, most patients may develop chronic renal failure, and the prognosis is poor (2).…”
Section: Introductionmentioning
confidence: 99%